Formulasi, Evaluasi dan Aktivitas Antioksidan Sabun Padat Serbuk Nano Teh Celup Bekas - Misbah Siregar; Minda Sari Lubis; Rafita Yuniarti; Zulmai Rani (Journal of Pharmaceutical and Sciences, 2025)
Background: Ideal soap should not only cleanse the skin but also contain substances that protect it from adverse effects, including those of free radicals, which can accelerate aging and cause other skin problems. Antioxidant compounds are needed to counteract free radicals. Used tea bags are a waste product that still contains antioxidant compounds. The use of nanotechnology is expected to enhance the stability and long-term effectiveness of cosmetic formulations, including soap. Objective: This study aimed to formulate a solid soap containing used nano tea bag powder, evaluate the physical characteristics of the soap, and test its antioxidant activity. Method: This research used a True Experimental method with a Post Test Only Control Group Design. The used tea bag powder sample was processed into nano powder using a Ball Mill. Solid soap was formulated in three variations: F0 (control without powder), F1 (containing 1.4% used tea bag powder), and F2 (containing 1.4% used nano tea bag powder). The soap preparations were then evaluated for their physical characteristics (organoleptic, pH, foam stability, hardness, cleaning power) and tested for antioxidant activity using the DPPH method. Results: The used tea bag powder was successfully converted into nano powder with an average particle size of 684.35 nm. Phytochemical screening results showed that both the powder and nano powder contained alkaloids, steroids, flavonoids, saponins, and tannins. Evaluation of the solid soap showed that all formulas (F0, F1, F2) met the physical quality requirements. The antioxidant activity test yielded IC50 values for F0, F1, and F2 of 975.2861 µg/ml (very weak), 211.3533 µg/ml (very weak), and 168.3053 µg/ml (weak), respectively. Conclusion: It can be concluded that the used tea bag powder meets the characteristics of nano powder. The solid soap formulation containing used nano tea bag powder meets physical quality requirements and demonstrates antioxidant activity, albeit in the weak category. The F2 formula (nano powder) showed better antioxidant activity than F1 (coarse powder) and F0 (control).